Information Technology Governance Audit at the Communication and Information Office of Central Lombok Regency Using the COBIT 2019 Framework - Sumiati; Joni Saputra; Ahmad Fatoni Dwi Putra (CV. Abhinaya Indo Group, 2025)
Information technology is widely used to enhance the ability to deliver, manage, and distribute information. The objective of this study is to assess the capability and maturity levels as well as to provide recommendations and suggestions. This research was conducted using the COBIT 2019 framework standard. Among the process objectives, three relevant objectives were selected: APO07, APO08, and APO12. The results of the study indicate that APO07 is at capability level 1 with a maturity score of 79.62%. APO08 has a maturity score of 80%, while APO12 has a maturity score of 74.99%. All three objectives fall within the evidence work of product category “Largely Achieved” (50–84%).